KETAHANAN EKONOMI DAN DAYA LENTING IBU RUMAH TANGGA DI KAMPUNG KUE SURABAYA PADA MASA PANDEMI COVID 19 - Maria Serlina Jaura; Azizah Alie; Yelly Elanda (Journal of Urban Sociology, 2022)
This article examines the economic resilience of families and the resilience of housewives during the covid 19 pandemic. The COVID-19 pandemic has shaken the economy of housewives in the cake village where the majority of their jobs are cake makers and sellers. The existence of a large-scale social restriction policy (PSBB) caused the turnover of cake sales to decline. The type of method used in this research is qualitative with a narrative approach. Data were obtained through observation and in-depth interviews with housewives who were involved in the production process (cake makers) and cake distribution (cake sellers). This study uses the theory of rational choice expressed by James Coleman. The results of this study indicate that the economic resilience of the family of housewives in the kue village was shaken due to the covid 19 pandemic. Housewives in the cake village only relied on the sales of cakes so that the family's economic resilience was increasingly vulnerable during the covid 19 pandemic. The resilience carried out by mothers households in the cake village during the covid 19 pandemic are (1) selling pastries so that the cake has a long expiration date; (2) relying on social media in marketing their products; (3) tighten belts or be frugal; (4) ask for help to their nearest social network.Keywords: Economic Resilience, Resilience, Kampung Kue, Covid 19 Pandemic